Analysis of Coxsackievirus B5 Infections in the Central Nervous System in Brazil: Insights into Molecular Epidemiology and Genetic Diversity - Raiana S. Machado; Francisco Gomes-Neto; Maria L. Aguiar-Oliveira; Fernanda M. Burlandy; Fernando N. Tavares; Edson E. da Silva; Ivanildo P. Sousa (Viruses, 2022)
Coxsackievirus B5 (CVB5) is one of the most prevalent enteroviruses types in humans and causes annual epidemics worldwide. In the present study, we explored viral genetic diversity, molecular and epidemiological aspects of CVB5 obtained from cerebrospinal fluid and stool samples of patients with aseptic meningitis or acute flaccid paralysis, information that is still scarce in Brazil. From 2005 to 2018, 57 isolates of CVB5 were identified in the scope of the Brazilian Poliomyelitis Surveillance Program. Phylogenetic analyses of VP1 sequences revealed the circulation of two CVB5 genogroups, with genogroup B circulating until 2017, further replaced by genogroup A. Network analysis based on deduced amino acid sequences showed important substitutions in residues known to play critical roles in viral host tropism, cell entry, and viral antigenicity. Amino acid substitutions were investigated by the Protein Variation Effect Analyzer (PROVEAN) tool, which revealed two deleterious substitutions: T130N and T130A. To the best of our knowledge, this is the first report to use in silico approaches to determine the putative impact of amino acid substitutions on the CVB5 capsid structure. This work provides valuable information on CVB5 diversity associated with central nervous system (CNS) infections, highlighting the importance of evaluating the biological impact of certain amino acids substitutions associated with epidemiological and structural analyses.